Developing Basic Football Techniques Model in Football Schools - Arsil Arsil; Anton Komaini; Sri Gusti Handayani; Heru Andika; Muhamad Ichsan Sabillah (Central European Journal of Sport Sciences and Medicine)
In this study, a basic football training model for students at Padang football schools is developed. The method employed in this research was research and development on the basis of Borg and Gall’s references; data from needs analysis were collected and then used to create a training model. The data were analyzed statistically to determine the effectiveness of this model. The mean difference test (t-test) is utilized to determine the difference between the structurally controlled exercise group and the uncontrolled group. The sample in this study involved 32 football school students aged 11–12 years. After the entire research process was conducted, a basic game-based training technique model was generated, which was named the Football Basic Technique Training Model. The results of data analysis and interpretation show that (1) the model follows the principles of necessary skills training in playing football; (2) it is useful to be used to optimize the basic technical skills of playing football; and (3) it can be applied as a guide in carrying out the training process, especially for children aged 11–12 years